KAJIAN PENERAPAN KONSEP TDRs SKEMA KOMPENSASI NON FINANSIAL PADA KAWASAN KUMUH DI KELURAHAN SEKAYU - Pangaribuan, Bosman; Haryanto, Ragil (Magister Pembangunan Wilayah dan Kota,Undip, 2019)
Handling of slum areas, especially â€œKampung Kotaâ€, should no longer be carried out by conventional means. Gentrification in kampung kota often occurs because of limited land in urban areas. Vertikal land consolidation which as one of Transferable Development Right with a non-financial compensation scheme expected as the solution on slums handled in urban areas. Apart from being able to help the government because of budget constraints, it can also help achieve better, organized and directed urban planning. Kampung Sekayu, as one of kampung kota inÂ Semarang, which as a slum area that experienced gentrification and increasingly caught up in the development around it. This study aims to examine whether the concept of Transferable Development Rights with non-financial compensation schemes with implementation vertikal land consolidation form, it can be a solution in slums handled and prevent the occurrence of gentrification in the area. This research method uses descriptive qualitative by field observations, in-depth interviews and, literature review, and secondary data as a complement to exploring information as much as possible and saw the reality in the field. Generally, a concept of vertikal land consolidation received a good response from stakeholders in Semarang City but related to non-financial compensation which generally given the form of zonation bonuses with excess building floors being constrained. it because of zoning permit arrangements in Semarang City which above 5 floors on the authority ofÂ Transportation Agency in relation to flight operation safety area (KKOP) of Ahmad Yani Airport in Semarang City. Non-financial compensation scheme that most beneficial to ease of licensed from Semarang city government..